One great speech : secrets, stories, and perks of the paid speaking industry (and how you can break in) - Reilly, James Marshall (Naperville, Illinois : Sourcebooks, 2020)
"Combining the career aspiration of The 4-Hour Workweek with the industry-specific insider take of Kitchen Confidential, One Great Speech is the first book to take readers inside the exciting world of the paid speaking industry. Aspiring speakers will find that, with the right know-how, anyone can harness the power of this career path. James Marshall Reilly demonstrates how the principles he used to generate millions of dollars in this fast-paced, high-pressure industry can be applied by anyone searching for paid speaking success. This industry has changed countless lives. With Reilly disclosing closely guarded industry knowledge, your life-changing moment could be here! Packed with engaging case studies, tips, and inside information on this largely unregulated industry, One Great Speech is the only complete resource that teaches you the ins and outs of the world of paid speaking"--
Show me the money : how it all works -- Come join the paid speaking party : why not you? -- But what if I'm a poet or a beekeeper? : Create your own lane -- How to avoid the most common mistakes : never mistake motion for action -- How to create your speaking topics : change the frame, change the game -- The art of the speaker bio : there are a million ways to tell the same story -- Collateral advantage : wrap yourself in quality -- All together now : how to make 1 1 = 3 -- How to get a speaking agent : finding the perfect fit -- What your agent actually does ... and how knowing that will help you -- Find your audience : what shelf do you sit on? -- How to set your rate : what are you worth? -- How to prepare for your first paid speech : ...and your second and third -- After the speech : how can you leverage the talk you just gave going forward? -- But what if I tried and failed? Be resilient and persevere -- Conclusion: One great speech : the million-dollar balloon.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Public speaking -- Vocational guidance; Electronic books